Nightmare In Red:The McCarthy Era In Perspective - Fried, Richard M. (Oxford Univ Pres New York, 1990)
Seeks to provide a rounded history of the rise and fall of McCarthyism. Traces the path os anti-Communist extremism across four decades to today and shows the impact on politics and culture.
First Oxford University Press paperback printing, 1991.
Keywords: McCarthy, Joseph -- 1908-1957; Anti-communist movements -- 20th century -- United States; Politics and government -- 1945-1953 -- United States; Politics -- 1945-1953